Improving Environmental Care Attitudes through Education on Proper Waste Disposal in Elementary School Children - Susanto, Setyo Budi; Rhafinda Nurcahyo Nugroho (Journal for Research in Public Health, 2026)
Environmental cleanliness remains a major challenge in many elementary school environments. Lack of student awareness of the importance of disposing of waste properly can negatively impact the cleanliness and health of the school environment. This study aims to determine the improvement of environmental awareness through education on how to properly dispose of waste in elementary school children. This study used a pre-experimental one group pretest-posttest design with a sample of 42 students in grades IV–VI selected through total sampling. The instrument was a knowledge and attitude questionnaire, while data analysis used the Wilcoxon Signed Rank Test. The results showed a significant increase after education. Before the intervention, the majority of students had low knowledge and attitudes. After education, 97.6% of students were categorized as having good knowledge and 76.2% had good attitudes. The statistical test yielded p <0.05, indicating the effect of education on improving students' knowledge and attitudes. The conclusion of this study is that education on disposing of waste properly is effective in fostering environmental awareness from an early age, and can be an important strategy in character education in elementary schools.